Management of full-thickness skin grafts. Issue 6 (2nd November 2021) - Davis, Mitchell; Baird, Daniel; Hill, Dane; Layher, Heather; Akin, Russell
Abstract: Full-thickness skin grafts are a commonly used reconstructive method following Mohs micrographic surgery. The literature varies on the most appropriate methods of suturing and securing grafts as well as best practices to dress the graft postoperatively. Our objective was to review various approaches to management of full-thickness skin grafts, including suturing the graft, securing the graft, and topical emollient use on the graft postoperatively. It was found that absorbable sutures, plain gut, provide preferable outcomes with full-thickness skin grafts. The tie-over bolster is the most-used method for securing skin grafts after placement, although several other methods have demonstrated efficacy, including the polyurethane foam, sandwich, and quilting suture methods. While various topical emollients are used in the immediate postoperative period, plain white petrolatum is the least likely to form allergic contact dermatitis.